A Differentiated Approach to Plant Variety Protection in Africa. (4th March 2016) - De Jonge, Bram; Munyi, Peter
Abstract : Several African countries and regional organizations are investing in the establishment of a plant variety protection system modeled on the UPOV 1991 Convention, which currently provides the strongest, international standard for plant variety protection. Whereas proponents argue that strong protection of breeder's rights will incentivize breeding and the introduction of new varieties for farmers, opponents fear that the proposed legal framework is unsuitable for African countries as it may hamper traditional farming practices of using and exchanging farm‐saved seed. These informal or farmer‐managed seed systems supply more than 80% of the total food crop seed used by farmers. The challenge for African countries is to strike a balance between protecting the interests of breeders through the incentive function of plant breeder's rights for the commercial market, and the leeway that needs to be provided to smallholder farmers that depend on informal sources for their seed security and survival. And to do so in a practical and legally enforceable manner. This paper explores how African countries and regional organizations can establish such balance through a differentiated approach to plant variety protection, which sets different levels of protection for different crops in relation to different categories of farmers.